The Realities of WorkThe Realities of Work, by Noon Mike and Blyton Paul. London: Macmillan, 1997. - Coleman, Lucretia (Academy of Management Review, 1999)
Mike Noon and Paul Blyton, in their book ‘The Realities of Work,’ effectively review varied and conflicting views on issues in today's changing workplace. The authors propose that no single representation of work is adequate to explain the changes that are occurring. New technology, new forms of organization, and new thinking in management all are factors that contribute to the transformation of the workplace. Noon and Blyton adopt a pluralistic perspective in their examination of six areas they have identified as ‘key tensions in the study of work.’ They attempt to balance theoretical and empirical orientations without minimizing the value of either.